Unimodality polynomials and generalized Pascal triangles - Ahmia, M.; Belbachir, H. (Algebra and Discrete Mathematics, 2018)
This paper is an extension of Boros and Moll’s result “A criterion for unimodality”, who proved that the polynomial P(x + 1) is unimodal.